Geotechnologies applied to the assessment of biophysical parameters of the Pantanal biome - Andrade, Ricardo Guimarães; Sediyama, Gilberto Chohaku; da Paz, Adriano Rolim; Lima, Evaldo de Paiva; Facco, Alexandro Gomes (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate surface biophysical parameters of the Pantanal biome, Brazil, by the application of geotechnologies. The Sebal algorithm, Modis imagery, and land use and land cover map were used. The obtained results for NDVI, surface temperature, albedo, daily sensible heat flux, daily net radiation and daily actual evapotranspiration were consistent with literature data for the different land use and land cover classes, and corroborate the analytical and synoptic capacity of Sebal estimates. These results show the potential of geotechnologies in the implementation of models or algorithms developed for the understanding of biophysical process dynamics related to the soil‑plant‑atmosphere interactions in Pantanal.